470 Robotic Transcranial Doppler With Artificial Intelligence for Real-Time Intraoperative Neuromonitoring During Endovascular Carotid Revascularization – A Novel and Autonomous Neuromonitoring Tool. (April 2023) - Baig, Ammad; Cappuzzo, Justin Mark; Monteiro, Andre; Khawar, Wasiq; Waqas, Muhammad; Donnelly, Brianna; Davies, Jason; Levy, Elad I.; Siddiqui, Adnan Hussain
Abstract : INTRODUCTION: Real-time intraoperative neuromonitoring is crucial to account for cerebral blood flow and embolic protection offered by proximal and distal cerebral protection devices during carotid revascularization procedures. METHODS: All patients diagnosed with high-grade carotid stenosis were prospectively enrolled between October 2021 thru February 2022. The TCD Robot head-brace system was used to secure the patients head, and the robot calibrated to automatically identify ipsilateral MCA or the terminal ICA. Patient demographics and procedural characteristics relevant to the robotic system such as signal strength, time to find signal, intracranial depth of the relevant vessel, cerebral waveform, and emboli count were recorded for the 4 critical phases: i- Access to crossing the lesion, ii- Filter and balloon deployment, iii- Stent placement and implantation, and iv- Removal of delivery system. RESULTS: Eight patients were included in our study (6 males [75%]; mean age 71.5 ± 3.9). Six out of 8 patients were symptomatic with a mean diameter stenosis of 83.5 ± 4.1. Average time taken to find a stable signal was 62 seconds (Range: 10-122). Terminal ICA was the vessel identified in all cases with a mean depth of 64mm (Range: 59-71). Flow arrest was demonstrated in all cases with flow reversal demonstrated in 2. Mean duration for the TCD Robotic surveillance was 23.6 ± 0.9 minutes with an average of 117 distal emboli (Range: 45-143) recorded by the device. Linear regression model identified stent placement and implantation as statistically significant (P = 0.0419) contributor to the final emboli count. CONCLUSIONS: To our knowledge, this is the first case series of real-time comprehensive neuromonitoring using a Robotic Transcranial Doppler system with Artificial Intelligence demonstrating various cerebral blood flow parameters including flow arrest and distal embolic incidence intra-operatively.